Comitant Ocular Deviation in Myasthenia Gravis. Issue 4 (December 2021) - Pike-Lee, Tiffany; Hill, Jeremy; Li, Jianbo; Kosmorsky, Gregory S.; Li, Yuebing
Abstract : Background: Occurrence of comitant ocular deviation in myasthenia gravis (MG) is not well described. Methods: A retrospective analysis of patients with ocular or generalized MG evaluated at a neuro-ophthalmology clinic for a 6-year period. Comitant ocular deviation was defined as magnitude of deviations in all planes varying by <20% from the measurement in the primary position. Results: Among the 120 patients included, 89 patients had ocular and 31 patients generalized MG. At the initial strabismus testing, comitant ocular deviation was present in 27 (22.5%) patients. Among the 16 patients who had a follow-up, ocular deviation remained comitant in 6 patients and converted to incomitant or no ocular deviation in 10 patients. An additional 7 patients demonstrated comitant ocular deviation at follow-up. Brain MRI was performed in 18 patients with comitant ocular deviation, and none showed abnormalities in the brainstem or cerebellum. Conclusion: Comitant ocular deviation can be an ocular manifestation of MG. Its presence does not necessarily indicate a central etiology in patients with MG neither excluding a MG diagnosis.